The Development of an Educational Statistics Module Based on a Guided Discovery Learning Model Oriented to Students’ Statistical Literacy - Hafiz, M; Dimyati, Ahmad; Putri, Finola Marta (Jurnal Pendidikan Matematika, 2024)
The low statistical literacy of students encourages lecturers to develop lecture modules that can facilitate this ability. This study aims to determine how to create a feasible, practical, and effective educational statistics module and identify the feasibility, practicality, and effectiveness of the Guided Discovery Learning-based educational statistics module to facilitate students’ statistical literacy. This type of research is Research and Development (R&D) with Plomp design with the stages of Preliminary Investigation, Design, Realization, and Evaluation. The trial subjects in this study consisted of two types, namely expert trial subjects and product trial subjects. The expert trial subjects were three lecturers of the Mathematics Education Department in one of The State University in Jakarta, while the product test subjects were seven mathematics education students in semester 4. Expert trial were conducted to assess the validity or feasibility of the products developed. The product trial was a limited trial to evaluate the practicality and effectiveness of the developed product. The results showed that the developed module met the feasible, very practical, and effective criteria. This research produces a module that can be used in statistics lectures to facilitate students’ statistical literacy. Rendahnya literasi statistika mahasiswa mendorong dosen untuk mengembangkan modul perkuliahan yang dapat memfasilitasi kemampuan tersebut. Penelitian ini bertujuan untuk mengetahui cara membuat modul statistika pendidikan yang layak, praktis, dan efektif serta mengetahui kelayakan, kepraktisan, dan keefektifan modul statistika pendidikan berbasis Guided Discovery Learning untuk memfasilitasi literasi statistik mahasiswa. Jenis penelitian ini adalah penelitian pengembangan atau Research and Development (R&D) dengan desain Plomp dengan tahapan Preliminary Investigation, Design, Realization, Evaluation. Subjek uji coba pada penelitian ini terdiri dari dua jenis, yaitu subjek uji ahli dan subjek uji coba produk. Subjek uji ahli adalah tiga orang dosen Jurusan Pendidikan Matematika di salah satu Universitas Negeri di Jakarta, sedangkan subjek uji coba produk adalah tujuh orang mahasiswa pendidikan matematika semester 4. Uji coba ahli dilakukan untuk menilai kevalidan atau kelayakan produk yang dikembangkan. Uji coba produk merupakan uji coba terbatas untuk mengevaluasi kepraktisan dan keefektifan produk yang dikembangkan. Hasil penelitian menunjukkan bahwa modul yang dikembangkan memenuhi kriteria layak, sangat praktis dan efektif. Penelitian ini menghasilkan modul yang dapat digunakan dalam perkuliahan statistika untuk memfasilitasi literasi statistik mahasiswa.